Dynamic performance of dielectric elastomer balloon incorporating stiffening and damping effect - Lv, Xiongfei; Liu, Liwu; Liu, Yanju; Leng, Jinsong (Smart materials and structures, 2018)
Dielectric elastomer (DE) balloon is a new type of actuator that can be used as high frequency pumps or loudspeakers. In this paper, a theoretical model of DE balloon, incorporating stiffening and damping effect, is developed. The numerical results, such as stretch-time curves, phase diagrams and Poincaré maps, are presented to study the influence of stiffening and damping on its dynamic performance. Taking the damping effect into account, the DE balloon can reach the equilibrium state after attenuation when subject to an instantaneous constant voltage; subject to a ramping voltage, the dynamic response presents three obvious stages: steady deformation, snap-through or snap-back, and damped oscillation. Due to the strain stiffening, the DE balloon may have two different stable equilibrium states and each has its own natural frequency. With small perturbation energy, the DE balloon can oscillate steadily around the two equilibrium states and resonate at multiple excitation frequencies. With large perturbation energy, the steady oscillation may transform into chaos. The damping force, however, changes no matter steady or chaotic oscillation into a constant periodic oscillation, and also determines the oscillation position.